2015
DOI: 10.1007/s11010-015-2446-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch activates mammalian target of rapamycin and AMP-activated protein kinase pathways in skeletal muscle cells

Abstract: Cellular protein synthesis is believed to be antagonistically regulated by mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) signaling pathways. In the present study, we examined the relationship between mTOR/p70 S6 kinase (p70S6K) and AMPK in response to mechanical stretch. C2C12 myoblasts were grown on a silicone elastomer chamber to confluence and further cultured in differentiation medium for 4 days to form multinucleated myotubes. Cells were subjected to 15% cyclic uniaxial stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Similar paradoxical observations have been described in previous studies ( Ng et al, 2012 ; Nakai et al, 2015 ). In an extracellular matrix detachment model, Ng et al (2012) demonstrated that after detachment AMPK is activated in both K-Ras V12-transformed and non-transformed mouse embryonic fibroblasts; interestingly, mTORC1 activity only decreased, in an AMPK-dependent manner, in transformed but not non-transformed fibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…Similar paradoxical observations have been described in previous studies ( Ng et al, 2012 ; Nakai et al, 2015 ). In an extracellular matrix detachment model, Ng et al (2012) demonstrated that after detachment AMPK is activated in both K-Ras V12-transformed and non-transformed mouse embryonic fibroblasts; interestingly, mTORC1 activity only decreased, in an AMPK-dependent manner, in transformed but not non-transformed fibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…Several cyclic stretching-induced effects have been discussed previously, such as cell proliferation, the disruption of cell-cell communication, and microtubule reorganization [24,[59][60][61]. These biological functions are activated by different signaling pathways [13,60,[62][63][64]. However, the cyclic stretchinginduced global phosphoproteome remains lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Trolox (Sigma-Aldrich, Italy, 0.1 mM) was used as a positive control for the antioxidant effect as described in Sestili et al [15]. Aminoimidazole-4-carboxamide ribonucleotide (AICAR, Sigma-Aldrich, Italy) was used (2 mM for 1 h) as a positive control for AMPK activation [31]. …”
Section: Methodsmentioning
confidence: 99%